PENGEMBANGAN BAMBOOZLE BASED MULTIMEDIA (BESTIE) PADA PEMBELAJARAN IPA DI SEKOLAH DASAR - Ardya Maharani, Shella Rantika; Bagus Amirul Mukmin; Kharisma Eka Putri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
In science subjects, students have difficulty in remembering the material and have low group discussion skills. This material requires visual media such as images and animations so that concepts can be understood more concretely. Science learning should use technology-based media. This study aims to determine the need assessment, validity, effectiveness, and practicality of Bamboozle-based multimedia. The method used is research and development (R&D) with the ADDIE model which includes stages: Analyze, Design, Development, Implementation, and Evaluation. The research was conducted at SDN 2 Bangunmulyo Pakel District with 20 students as the subjects. Data collection techniques include need assessment, expert validation, pretest and posttest, and practicality questionnaire. The data analysis technique used the average percentage of needs questionnaires by students and teachers, the average percentage of questionnaires from material experts and media experts, the N-Gain test based on student pretest and posttest results, and the average percentage of student and teacher practicality questionnaires. The results showed that the need assessment showed a value of 88.6% with very need criteria, the validity test obtained an overall average value of 91.9% with very valid criteria, the effectiveness of obtaining an N-Gain value of 0.89 with a high category means very effective, and the practicality test results reached 88.6% with very practical criteria. Therefore, this media is recommended to be applied.